ENVIRONMENTAL EDUCATION AS A STRATEGY FOR THE PROMOTION AND PROTECTION OF CHILDREN'S MENTAL HEALTH - da Silva, Leidyane Alves; Barreto, Alyne Anne Silva; Pires, Débora de Jesus (Seven Editora, 2025)
Children's mental health is essential for children's integral development, but factors such as stress, excessive use of technology, and lack of contact with nature can compromise this balance. This research aimed to review the literature on the relationship between Environmental Education and child mental health, analyzing the benefits of this approach for children's emotional and cognitive development. The literature review considered the search for scientific articles in the Web of Science, Lilacs, and Scielo databases, in the period from 2020 to March 1, 2025. The descriptors used were Environmental Education, Environmental Literacy, Mental Health, Psychological Well-being, Emotional Development, Child, Child Development, and Outdoor Education, combined by the Boolean operator AND. A total of 19 scientific articles were identified, but after applying the inclusion and exclusion criteria, only eight were selected. The studies analyzed indicate that exposure to natural spaces reduces stress and anxiety, in addition to improving children's creativity, concentration, and school performance. The results indicate that active methodologies aimed at outdoor learning can contribute significantly to the strengthening of children's mental health. However, challenges in the school environment, such as the lack of adequate infrastructure and the need for specific teacher training, still limit its implementation. In addition, the absence of projects promoted by the Department of the Environment and the excessive use of screens by both family members and children reduce contact with nature. Given this scenario, it is essential to adopt policies that encourage the creation of green spaces in schools, the continuous training of teachers, and social projects that promote children's contact with nature. Thus, it is concluded that Environmental Education plays a fundamental role in the promotion and protection of children's mental health, contributing to a more balanced and healthy childhood.DOI: https://doi.org/10.56238/sevened2025.021-005